PENGARUH FRAUD RISK FACTOR DENGAN PENDEKATAN FRAUD PENTAGON TERHADAP KECURANGAN LAPORAN KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Nico Aditya Pradana (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2019)
The aim of this study is to examine the effect of pentagon fraud theory, which is proxied by financial targets, financial stability, external pressure, institutional ownership, ineffective supervision, quality of external auditors, change of auditors, change of directors and frequent number of CEO pictures on fraudulent financial reporting that is proxied using F- Score. The study used the purposive sampling method with the sample criteria being manufacturing companies listed on the Indonesia Stock Exchange (BEI) in the period from 2016 to 2018. Based on these criteria, a sample of 85 companies was obtained for the three-year financial statement period. This research was conducted with a quantitative approach, using the analysis technique of multiple regression analysis with SPSS. The results showed that the variable financial targets, financial stability, external pressures, the nature of the industry, the quality of external auditors and changes in external auditors significantly influenced fraudulent financial reporting. Keywords: fraud pentagon, fraudulent financial reporting, F-score, financial target, financial stability, external pressure, institutional ownership, ineffective monitoring, nature of industry, quality of external audit, change in auditor, change in directors, frequent number of CEO pictures.